2008
DOI: 10.1063/1.2903071
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and structural ordering on a bcc lattice for highly magnetostrictive Fe–Ga alloys: A coherent potential approximation study

Abstract: We calculate the electronic structure, magnetic moments, and ordering energies of highly magnetostrictive Fe 1−x Ga x alloys from first-principles in the composition range up to x = 0.25. The coherent potential approximation was used to treat effects of chemical disorder. Given an underlying bcc lattice in whole range compositions investigated, the DO 3 type of ordering is found to have a lower energy than A2-and B2-type structures. We find that ordering energies strongly depend on the state of magnetic order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
2
25
1
Order By: Relevance
“…The DOS panels for Fe 3 Fe agree well with earlier calculations ͑in the A2 structure͒. 15 The present calculations therefore show clearly the appearance of an additional peak for minority spins in Fe 3 Ga resulting from the formation of Ga-Ga pairs in the bcc Fe host ͑indicated by an arrow in Fig. 5͒.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The DOS panels for Fe 3 Fe agree well with earlier calculations ͑in the A2 structure͒. 15 The present calculations therefore show clearly the appearance of an additional peak for minority spins in Fe 3 Ga resulting from the formation of Ga-Ga pairs in the bcc Fe host ͑indicated by an arrow in Fig. 5͒.…”
Section: Resultssupporting
confidence: 79%
“…11 A further splitting of this peak is exactly the reason claimed by Wu 11 for the large magnetoelastic coupling in the L6 0 structure, although a single-site CPA study used for the description of substitutional atomic disorder does not predict any such splitting. 15 It has been also pointed out that this splitting is not an averaged property of the particular chemical ordering, but rather a local environment effect and a result of the lowering of the local symmetry around the Fe atom, and besides, it is argued that it is not quite clear how this symmetry lowering should be caused entirely by the existence of ͗100͘ Ga-Ga pair ordering. 15 Nevertheless ordering energies strongly depend on the state of magnetic order and in Galfenol it has been reported that thermal magnetic disorder strongly favors chemical ordering DO 3 and B2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our reflection high energy electron diffraction (RHEED) measurements during film deposition indicate that the structural quality of the Ga x Fe 1−x does not dependent significantly on the Fe concentration, i.e., structural disorder cannot account for the reduction of In epitaxial EuO thin films, the Eu M 5,4 XMLD shows only a very small angular dependence, which could be explained by the nearly perfect spherical shape of the half filled Eu 4f shell [21]. For Ga x Fe 1−x , Lei et al [10] calculated the anisotropy of the Fe 3d orbitals for D0 3 , B2-like, and L1 2 lattice structures [11]. They showed that the D0 3 structure has an almost isotropic 3d charge density and that there is hardly any difference between the two Fe sites in this lattice structure.…”
mentioning
confidence: 99%
“…For x ≥ 0.3, the Fe L 3 XMCD decreases almost linearly with Fe concentration. It is generally accepted that hybridization of the Fe and Ga states reduces the Fe magnetic moment [9][10][11][12]. Detailed calculations aimed at determining the concentration dependence of the Fe moment in different lattice structures and sites have been performed.…”
mentioning
confidence: 99%